SCIENTIFIC-PRACTICAL ANALYSIS OF THE PRIVATIZATION METHODS OF NON-AGRICULTURAL LAND PLOTS - Raxmatillaev Jasurbek Raxmatilla og‘li (Scholar Express Journals, 2023)
In this article, methods of privatization of non-agricultural land plots are scientifically and practically analyzed. Also, the analysis of views of scientists on the methods of privatization of non-agricultural land plots, the analysis of legal norms, the types of land plots and immovable property located on them, the determination of their legal status, and the problems of establishing absolute state ownership of land plots until now have been revealed..
Keywords: non-agricultural land plot; privatization; privatization method, state ownership; types of real estate